Pemodelan hidrologi - hidraulik aliran air songsang dan analisis saiz partikel sedimen Sungai Chini, Pahang - Mohd Ekhwan Toriman,; Mohd Khairul Amri Kamarudin,; Nor Azlina Abd Aziz,; Muhamad Barzani Gasim,; Mushrifah Hj Idris,; Nor Rohaizah Jamil, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
Backwater flow refers to the occurrence of abnormal flood waters causing by inflow water from major to tributary streams. At Sungai Chini, inflow from Sungai Pahang brings high suspended sediments which contributed to active sediment fine deposition. This article discusses the results on sediment size determination that was carried out in Sungai Chini in two different seasons, namely normal season (16/8/08) and rainy season (4/12/08). Three sampling stations were selected. Parameters used in this study are based on grain size distribution (g). Different size of material classifications were determined and calculated using Phi scale (ø) in order to calculate their median, mean (M), standard deviation (D) and skewness (S). River flow estimation (m3/s) and some other hydraulic data were also calculated for modeling and simulation using XP-SWMM software. Simulations carried out aimed to evaluate the actual flow that occurred during the study period as well as to identify current problems that arise. The results indicate that the grain sizes as showing in mean’s statistic is rough grain with phi ø 0.00 to phi ø 1.00. Meanwhile, the standard deviation (D) indicates of poor and very poor deposition, between phi ø 1.00 to phi ø 4.00, and skewness (S) shows grains size between moderate to very fine, which is between phi ø +0.10 to phi ø +1. 00